(untitled) (Bangladesh Journal of Medical Science, 2014)
Introduction: Femoral neck fractures are rare injuries in children, but the high incidence of long term complications make it an important clinical entity. The aim of this prospective study was to analyze the clinical outcomes of pediatric femur neck fractures. Methods: The study included 16 children (10 boys and 6 girls) who sustained femoral neck fractures and completed an average follow-up of 28 months. The children were treated with anatomical reduction and internal fixation with partially threaded cancellous screws. The outcomes were clinically and radio logically assessed for fracture healing, joint movements and implant failure. Results: The mean age of included patients was 10 years (range, 6 to 16 years) and the average followup was 28 months (range, 17 -48 months). Coxa- vara was the most common complication Other complications included nonunion associated with Partial a vascular necrosis and delayed union was seen in one case but later on it had been corrected. Two cases of slight coxa vara were seen radiologically but clinically patients had no problem in walking and daily activities. All children achieved union in a mean time of 10 weeks (range from 6 - 16 weeks) except two cases. Full weight bearing was possible in a mean time of 8.8 weeks. The results were excellent in 68.75% and good in 18.75% patients. Conclusions: We conclude that the early operation using anatomical reduction and internal fixation of pediatric femoral neck fracture offers the best results and provide early healing less complication with good results and is economical. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18303 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.198-204